Fusarium diversity from the Golden Gate Highlands National Park - Steyn, Carla; Jacobs, Adriaana; Summerell, Brett; Venter, Eduard (Frontiers in Microbiology, 2023)
Members from the genus Fusarium can infect a broad range of plants and threaten agricultural and horticultural production. Studies on the diversity of Fusarium occurring in natural ecosystems have received less attention than the better known phytopathogenic members of the genus. This study identified Fusarium species from soils with low anthropogenic disturbance found in the Golden Gate Highlands National Park (GGHNP), a part of the Drakensberg system in South Africa. Selective techniques were implemented to obtain 257 individual isolates from the selected soil samples for which the translation elongation factor 1α (tef-1α) gene region was sequenced and compared against the Fusarium MLST and FUSARIUM-ID databases. Phylogenetic analyses, based on maximum likelihood and Bayesian inference, were used to determine species diversity in relation to reference isolates. Species level identifications were made within three of the seven species complexes and identified F. brachygibbosum, F. sporotrichioides, F. andiyazi, and F. gaditjirri based on the FUSARIUM-ID database, with F. transvaalense and F. lyarnte identified against the Fusarium MLST database. This indicated highly diverse populations of Fusarium from soils with low anthropogenic disturbance from the Afromontane grassland region found in mountain ranges.